Akses Keadilan bagi Kelompok Rentan: Studi Empiris Mengenai Hambatan Struktural dalam Sistem Peradilan - Polii, Valentino; Polii, Dian Julius (Universitas Sains dan Teknologi Komputer, 2025)
Access to justice is a fundamental right in a legal state, yet vulnerable groups in Indonesia still face various structural barriers in exercising this right. High litigation costs, complex legal procedures, and the limited availability of legal aid services significantly hinder their ability to seek justice. This study aims to identify the key obstacles faced by vulnerable groups in accessing the justice system and evaluate the effectiveness of existing legal aid policies. Using a qualitative approach with an empirical-sociological methodology, data were collected through in-depth interviews with legal aid providers, vulnerable individuals, and judicial officials, as well as a review of relevant legal documents and case studies. The findings reveal that 52% of vulnerable individuals are unaware of their rights to free legal aid, while 45% of domestic violence victims struggle to access legal protection due to procedural barriers. Additionally, 58% of cases involving low-income individuals were rejected due to administrative shortcomings. Statistical analysis further indicates a significant negative correlation between income levels and access to legal representation (r = -0.76, p < 0.05). These results highlight the urgent need for policy reforms to create a more inclusive and equitable legal system. This study contributes to the discourse on legal accessibility by providing empirical evidence on structural barriers and offering recommendations to enhance legal aid services, particularly through digital solutions and policy interventions tailored to the needs of vulnerable groups